The degree to which school principals practice the values of integrity from the point of view of female deputies in Taif Governorate - Al-Sofiani, Saleha Hai (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the degree to which school principals practice the values of integrity from the point of view of female deputies in Taif Governorate, in terms of reality and the problems that hinder adherence to them and methods of activating them, and the extent to which there are differences between the viewpoints of the sample depending on the variables: (academic qualification, years of experience, training courses The researcher used the descriptive survey method, and a questionnaire was distributed to a sample of (50) female agents, representing 20.66% of the study population.The results of the study revealed: that school principals practice the values of integrity to a high degree, with an average of (4.16), the problems axis came in at a moderate degree, with an average of (3.03), and methods had a high degree, with an average of (4.27), while the fourth axis showed that there were statistically significant differences between the female agents in the reality axis. The number of years of experience is in favor of more than 10 years, and there are no statistically significant differences in the number of training courses attended by female agents except in the problem area, and in favor of (more than 5 programs)The study recommended activating strict accounting and monitoring systems to ensure that female directors adhere to and implement the values of integrity, and provide training programs and periodic educational courses for female directors and agents. She suggested organizing a school information base that includes all documents to protect integrity and make available information available to those wishing to search for it.